DOP012 Disease demarcation in ulcerative colitis is associated with different patterns of gene expression. (16th January 2018) - Suarez-Farinas, M; Huang, R; Kosoy, R; Irizar, A; Losic, B; Wei, G; Peters, L; Song, W -m; Di Narzo, A; Wang, W; Perrigoue, J; Castillo, A; et al.
Abstract: Background: Disease extent varies in UC from proctitis (E1) to left-sided colitis (E2) and pancolitis (E3). When the extent of UC is limited there is a sharp demarcation between macroscopically involved and uninvolved areas, which remains unexplained. As 25% of limited UC patients extend over time, we assessed molecularly the mechanisms defining the anatomic delineation between affected and unaffected colon. Methods: We performed RNA-seq analysis on biopsies from UC patients and characterised inflammation at and proximal to the endoscopic demarcation of disease. We collected biopsies from endoscopically involved rectum (37), sigmoid (12) and left colon (9) of UC patients. Uninvolved areas, either directly adjacent to the inflamed site or more proximal were also sampled. The resulting 148 paired biopsies were then "ordered" by inflammation status and gut location and a "distance" from inflammation was assigned for each biopsy. The distance from the first adjacent region to the inflamed biopsy was defined as D = 1, for example, inflamed rectum and uninflamed sigmoid. A D = 2 was assigned if the adjacent biopsy was two regions away from the inflamed biopsy up to D = 5. Expression changes were modelled over all the distances from inflammation. Results: Two striking patterns of expression were observed. One included genes progressively changing expression as the distance from the site of inflammation increased ("slope geneset"). The second included genes abruptly changing expression at the first adjacent region to the inflamed biopsy and then not changing further ("wall geneset"). Slope genes decreasing in expression were inflammatory (IFNg, IL6 and Oncostatin-M), suggesting that the reach of inflammation was further than observed by endoscopy. However, a subset of inflammatory genes as well as integrins and adhesion molecules had sharply decreased expression at the adjacent uninflamed region (wall genes: IL23A, IL22, TNF, and IL10), suggesting that these may be important for modulating progression of disease. Upregulated slope genes included solute carrier and homeobox genes while upregulated wall genes included glucoronidation and fatty acid binding proteins, suggesting altered gut function. Conclusions: A complex molecular pattern exists at the "visible" line of disease demarcation. This may help to understand its origin and potentially provide biomarkers of UC extension.